Numerical modeling as supporting tool for aquaculture of oysters in a subtropical estuarine ecosystem - Fontes, Roberto Fioravanti Carelli [UNESP] (2019)
The Estuarine-Lagoon Complex of Cananeia-Iguape (ELCCI) is a large estuarine system dominated by mangroves, located on the southeast coast of Brazil (25° S, 48° W). Oyster farming is an important economic activity in Cananeia due to the natural abundance of oyster seeds originally found in its mangrove fields. The aim of this study was to describe the hydrodynamic aspects of the mangrove and oyster farming in the ELCCI by analyzing environmental scenarios using numerical simulations. Simulations allowed for the description of the distance of penetration of the salt wedge into the system as well as the direction and magnitude of the tidal currents. Higher values of river discharge corresponded to lower distances of penetration of the salt wedge, a feature which shows that the freshwater discharge and geomorphology together determine the variation in salinity within the estuary. Oysters are cultivated in regions of higher salinity and relatively stable conditions, with low speeds of tidal currents and little vertical variation in salinity. Under average river discharge conditions (450 m3.s-1), there is a confluence of tidal waves in Mar Pequeno, where velocity is lower. This change may lead to a higher sedimentation at restricted areas and thus to a higher deposition of organic matter derived from oyster cultivations during flood tides.